418 Clinical translation of methylated DNA markers of endometrial cancer using tampon-based detection. (13th November 2020) - Bakkum-Gamez, J; Sherman, M; Slettedahl, S; Mahoney, D; Lemens, M; Laughlin-Tommaso, S; Hopkins, M; VanOosten, A; Shridhar, V; Taylor, W; Staub, J; Cao, X; et al.
Abstract : Objective: In tampon samples from women with and without EC, we tested methylated DNA markers (MDMs) for EC originally identified through discovery and validation in tissue. Methods: From 2/2013–8/2019, women ≥45 yrs with abnormal or postmenopausal bleeding or biopsy-proven EC were prospectively enrolled for vaginal fluid collection via tampon before endometrial sampling or hysterectomy, respectively. ECs were frequency matched by menopausal status and tampon collection date to benign endometrium (BE) controls. Tampons were placed in preservative buffer; extracted DNA from cell pellet was bisulfite-converted and underwent methylated specific PCR for 29 top performing EC and other solid tumor MDMs (MAX.chr12.52652301, CDH4, EMX2OS, c17orf64, NBPF8, SFMBT2, JSRP1, DIDO1, MAX.chr10.22624479, MPZ, ZNF506, VILL, GATA2, MAX.chr14.103021656, CYTH2, LRRC8D, LYPLAL1, MAX.chr8.145103829, SQSTM1, ZNF323, OBSCN, MAX.chr9.36739811, ZNF90, LRRC41.8188, LRRC34, GDF7, MDFI, EEF1A2, SEPT9). Random forest modeling analysis performed to generate predictive probability of underlying EC. Results: 100 EC and 92 BE were enrolled. The 29-MDM panel highly discriminated between EC and BE (96% (95%CI 89–99%) specificity; 76% (66–84%) sensitivity (AUC 0.88). In 2/2017, the PBS-based tampon buffer was modified to include 50 mmol EDTA. The 29-MDM panel demonstrated greater sensitivity in tampon samples (57 EC; 52 BE) collected into PBS/EDTA buffer (96% (95% CI 87–99%) specificity; 81% (68–90%) sensitivity (AUC 0.90). Among endometrioid and serous histologies, the panel correctly identified 85% and 78%, respectively, and the majority of other subtypes (table 1 ). Conclusion: Top EC plus other solid tumor MDMs performed with promisingly high sensitivity and specificity in tampon-collected vaginal fluid. PBS/EDTA buffer improves sensitivity.